Ultrabithorax is a key regulator for the dimorphism of wings, a main cause for the outbreak of planthoppers in rice. Issue 7 (8th April 2020) - Liu, Fangzhou; Li, Xiang; Zhao, Muhua; Guo, Mengjian; Han, Kehong; Dong, Xinxin; Zhao, Jing; Cai, Wanlun; Zhang, Qifa; Hua, Hongxia
Abstract: Rice planthoppers, the most devastating rice pests, occur in two wing forms: the short-wing form for rapid population growth and long-wing form for long-distance migration, which together create the mechanism for outbreak. Here we show that Ultrabithorax ( Ubx) is a key regulator for switching between the long- and short-wing forms of rice planthoppers. Ubx is expressed in both forewing and hindwing pads, which is different from the canonical model of Ubx expression. In brown planthoppers, expression of Ubx ( NlUbx ) is regulated by nutritional status of the rice host. High-quality young plants induce NlUbx expression leading to the short-wing form; low-quality ripe plants reduce NlUbx expression resulting in long-wing form. We also showed that NlUbx is regulated by the insulin receptors NlInR1 and NlInR2. The default expression of NlInR1 inhibits NlUbx resulting in long-wings, while high-quality hosts induce NlInR2 expression, which represses NlInR1 thus promoting NlUbx expression to produce short-wings.